(untitled) - Dansk standard (Denmark, 1996)
The text of the international Standard ISO 14001:1996 has been prepared by Technical Commitee ISO/TC 207 "Environmental management" in collaboration with CEN/CS. this European Standard shall be given the status of a national standard, either by publication of an identicl text or by endorsement, at the latest by March 1997.
Keywords: Quản lý môi trường,Tiêu chuẩn ISO 14000,ISO 14000 Series Standards,Production management,Environmental management,Quản lý sản xuất; Tiêu chuẩn,Environmental aspects,Standards,Khía cạnh môi trường